Mapping Stratigraphy and Artifact Distribution with Unmanned Aerial Vehicle-Based Three-Dimensional Models—A Case Study from the Post Research Area in Northwestern Texas, USA - Stance Hurst; Eileen Johnson; Doug Cunningham (Drones)
This study applies UAV-based photogrammetry to map and examine the stratigraphy and archaeological artifact distribution in two localities within the Post research area in northwest Texas. A DJI Inspire 1 UAV equipped with a Zenmuse X5 camera captured nadir and oblique images. These were processed using Agisoft Metashape to generate 3D models. These models enabled the precise mapping of stratigraphic boundaries, revealing the distinctions between Triassic-age bedrock, Pleistocene-age alluvial deposits, and Holocene-age aeolian sediments. Field surveys from 2022 to 2024 documented over 5000 artifacts with sub-centimeter accuracy, including diagnostic projectile points and ceramics. This research highlights the advantages of UAV-derived 3D models in rapidly and accurately documenting stratigraphy and archaeological data. It demonstrates the value of UAV technology for visualizing landscape-scale processes and artifact contexts, offering a new approach to understanding the interactions between geomorphology and archaeology. The findings contribute to advancing UAV applications in both geomorphological and archaeological research.